Tratamento de água branca de indústria de papel por microfiltração e ultrafiltração - Cabral, Bruna Mulinari (2016)
The present study was as scope to evaluate and compare application of filter microfiltration and ultrafiltration membranes in the treatment of the paper industry’s white water. It were performed assays in pilot unit’s of microfiltration and ultrafiltration for a further comparative analysis of efficiencies apparent color removal, COD, suspended solids, sedimented solids and turbidity of white water. It was also evaluated the permeate flux values obtained on different experiments. After each assay, the membranes were subjected to chemical cleaning process with solution of the 1,0 g/L sodium hypochlorite. The results indicated that the micro and ultrafiltration membranes resulted in high removal efficiencies for the studied parameters: 78.26% of COD for MF and UF for 82.75%, 99.48% turbidity for MF and 99.09 % for UF, 97.18% removal of apparent color to 96.82% for MF and UF, this way, the treatments applied showed promising results on the paper industry’s treatment of white water.